Вплив ірраціоналізму А. Шопенгауера на творчість Р. Вагнера - Глюза, А. П. (ХНУРЕ, 2019)
The influence of irrational philosophy of A. Schopenhauer on the musical art of R. Wagner is considered in the article. Irrationalism laid a new trend in modem art, which changed the view on aesthetic values. The new approach was that the beauty in art should be sought not in the similarity with real life, but in yourself.